2023
DOI: 10.1021/acsomega.3c03774
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Human Serum Albumin Protein Corona in the Antimicrobial and Photothermal Activity of Metallic Nanoparticles against Escherichia coli Bacteria

Alexa Guglielmelli,
Patrizia D’Aquila,
Giovanna Palermo
et al.

Abstract: The emergence of antibiotic-resistant bacteria has become a major public health concern, leading to growing interest in alternative antimicrobial agents. The antibacterial activity of metal nanoparticles (NPs) has been extensively studied, showing that they can effectively inhibit the growth of various bacteria, including both Gram-positive and -negative strains. The presence of a protein corona, formed by the adsorption of proteins onto the NP surface in biological fluids, can significantly affect their toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Studies had been done to determine how varied NP sizes and surface charges affected the structural changes in serum proteins. However, they did not inquire how they affect the proteins’ activities. This calls for a thorough investigation into how the surface charge (plain, amine, and carboxylated) and size (lowest: 100 nm, highest: 500 nm) of NPs affect the enzyme activity of HSA.…”
Section: Resultsmentioning
confidence: 99%
“…Studies had been done to determine how varied NP sizes and surface charges affected the structural changes in serum proteins. However, they did not inquire how they affect the proteins’ activities. This calls for a thorough investigation into how the surface charge (plain, amine, and carboxylated) and size (lowest: 100 nm, highest: 500 nm) of NPs affect the enzyme activity of HSA.…”
Section: Resultsmentioning
confidence: 99%
“…Metal nanoparticles have been proposed as promising candidates for antimicrobial agents. Not only do they possess the ability to induce microbial death or limit growth, but they also exhibit unique physicochemical properties, including a high surface area-to-volume ratio, reactivity, and stability [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, interest in the biological and biomedical uses of NPs has increased sharply. In addition to their SERS and fluorescence applicability for biosensing [8] this is due to the already reported applications in therapy [9] and their antimicrobial activity [10]. The latter, combined with the increase in bacterial species resistant to antibiotics [11] forces biocompatibility and biotoxicity studies to be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, biocompatible gold NPs [17,18] are in a wider use for biological objects. Besides, it has recently been shown that the toxicity of gold, silver and platinum NPs can be significantly influenced by proteins contained in surrounding biological fluids [10].…”
Section: Introductionmentioning
confidence: 99%